War and diplomacy the Russo-Turkish War of 1877-1878 and the Treaty of Berlin - Yavuz, M. Hakan; Sluglett, Peter (Utah series in Middle East studies, 2011)
Combining different disciplinary perspectives, War and Diplomacy argues that the key events that portended the beginning of the end of the multiethnic Ottoman Empire were the The Russo-Turkish War of 1877-1878 and the Treaty of Berlin. The essays in this volume analyze how the war and the treaty permanently transformed the political landscape both in the Balkans and in the Caucasus. The treaty marked the end of Ottoman hegemony in the Balkans by formally recognizing the independence or de facto sovereignty of Romania, Serbia, and Montenegro, and the autonomy of Bulgaria